2019
DOI: 10.1109/access.2019.2951152
|View full text |Cite
|
Sign up to set email alerts
|

Ray Theory-Based Transcranial Phase Correction for Intracranial Imaging: A Phantom Study

Abstract: Ultrasonic imaging provides a non-invasive way to diagnose brain disease. However, due to imaging degradation effects from the phase-aberration and reverberation, it is still challenging to achieve an accurate transcranial imaging. The objective of this work is to improve the quality of transcranial imaging. To this end, a ray theory based transcranial phase correction method was proposed to correct the phase abberation induced by cranial bones. With the pre-knowledge of the shape and longitudinal velocity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…As a result, optimal focusing with the imaging transducer was limited to a region, at rather large depth (for the imaging transducer) close to the part of the skull in contact with the calibration transducer, and at lateral positions where the skull was sufficiently flat to enable close contact with the calibration transducer. Prior knowledge on the compressional sound speed or thickness of skull [53], [58], [76], [88], [89] and correction based on CT scans [53]- [55] are also impractical on-site as these parameters vary in person [23], [25], [29], [51], [52], [90], [93] and EMS are not always equipped with CT scanners.…”
Section: A Comparison With Previous Relevant Work 1) Estimating the C...mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, optimal focusing with the imaging transducer was limited to a region, at rather large depth (for the imaging transducer) close to the part of the skull in contact with the calibration transducer, and at lateral positions where the skull was sufficiently flat to enable close contact with the calibration transducer. Prior knowledge on the compressional sound speed or thickness of skull [53], [58], [76], [88], [89] and correction based on CT scans [53]- [55] are also impractical on-site as these parameters vary in person [23], [25], [29], [51], [52], [90], [93] and EMS are not always equipped with CT scanners.…”
Section: A Comparison With Previous Relevant Work 1) Estimating the C...mentioning
confidence: 99%
“…More recently, approaches that model refraction through the true geometry and thickness of the skull have been proposed; however, the method requires estimates of the thickness and wave speed in the skull at multiple positions with dedicated ultrasound measurements prior to image reconstruction [50]- [52]. Another family of methods relies on a CT or MRI scan of the skull to determine its geometry and knowledge or assumption of wave speed in bone, prior to TUI [53]- [56].…”
Section: Introductionmentioning
confidence: 99%
“…However, smarter homogeneous models can be used to improve computation time without losing too much accuracy. For example, Jiang et al 74 . showed that taking different averaged properties for the refraction computations and for the time‐of‐flight computations significantly improves the accuracy without increasing the computation time.…”
Section: Discussionmentioning
confidence: 99%
“…Phase aberration correction was first proposed by modeling the temporal bone as an infinitesimally thin aberrating layer at the surface of the transducer (so called the near-field phase-screen aberration model) [24][25][26], but the correction obtained by this approach is limited (axially and laterally) to a certain region called the isoplanatic patch [3,[27][28][29][30]. Another approach is using either ultrasound measurements [31][32][33] or CT/MRI scans of the skull to obtain the true geometry and sound speed of the temporal bone prior to image reconstruction, and then correct phase aberration and refraction during image reconstruction [34][35][36][37]. Recently, we have shown the feasibility of single-sided two-dimensional transcranial ultrasound through the human temporal window using a single handheld commercial probe, where the position, true geometry and sound speed of the bone layer were estimated for an accurate correction of phase aberration and refraction [38,39].…”
Section: Introductionmentioning
confidence: 99%